Comparative Analysis of Conventional PID Controller and Fuzzy Controller for Load Frequency and Voltage Control - Adhikari, Sahansil; Khatiwada, Rohan; Parajuli, Vision; Shrestha, Suraj; Alam, Afroz (Journal of Engineering and Sciences, 2022)
Abstract available with the full text.